THE ROLE OF TEST TECHNOLOGIES IN THE PROCESS OF TEACHING FOREIGN LANGUAGES IN SECONDARY SCHOOL (American Journal of Pedagogical and Educational Research, 2022)
This article examines the role of testing technology in the educational process, foreign languages, advantages of tests compared to traditional tests a form of control is shown.